(untitled) (International Journal of Engineering and Computer Science, 2017)
Reducing the time that a user has to occupy resources for completing cloud tasks can improve cloud efficiency and lower user cost. Such a time, called cloud time, consists of cloud deployment time and application running time. In this work we design jump-start cloud, under which an efficient cloud deployment scheme is proposed for minimizing cloud time. In particular, VM cloning based on disk image sharing has been implemented for fast VM and application deployment. For applications with heavy disk visits, the post-deployment quality of service (QoS) may suffer from image sharing and consequently, application running time will increase. To solve this problem, different image distribution schemes have been designed. We test jump-start cloud through a Hadoop based benchmark and MapReduce applications. Experiment studies show that our design saves application installation time and meanwhile, keeps application running time reasonably low, thus makes cloud time shorter.